18 billion at one blow: Evaluating Germany's twenty biggest tax expenditures - Michael Thöne (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2012)
“Periodically evaluating the size and effectiveness of tax expenditures is a necessary (although not sufficient) requirement for good government.” Leo Burman's appeal of 2003 is quoted often but followed seldom. The paper reflects on the evaluation of Germany's twenty biggest tax expenditures commissioned by the Federal Government in 2007 and completed by a team of three European research institutes in 2009. Based on a methodological framework developed for the uniform evaluation of dissimilar tax expenditures the research team worked through tax privileges worth more than 18 billion euro, i.e. 85 per cent of all official German tax subsidies. The analysis covered exemptions from corporate and personal income taxes, value-added tax (VAT) and energy taxes. To our knowledge, this was one of the biggest evaluations of tax expenditures ever concluded in the world. The paper discusses the common methodology applied in the evaluation; and the lessons learned from the research effort. It gives an overview of evaluation results and eventual policy lessons to be learned from them.
Keywords: H24; H25; 330; tax expenditures; tax subsidies; evaluation